Determination of sweetener specificity of horse gut-expressed sweet taste receptor T1R2-T1R3 and its significance for energy provision and hydration - Smith, Liberty; Moran, Andrew W.; Al-Rammahi, Miran; Daly, Kristian; Shirazi-Beechey, Soraya P. (Frontiers in Veterinary Science, 2024)
Studies carried out in several species have demonstrated that detection of low-calorie sweeteners in the lumen of the intestine, by the sweet receptor, T1R2-T1R3, initiates a signaling pathway leading to enhanced expression and activity of intestinal Na+/glucose cotransporter 1, SGLT1. This results in an increased gut capacity to absorb glucose, sodium chloride and water, the basis for oral rehydration therapy. Horses express T1R2, T1R3 and downstream signaling elements in the intestinal tissue. As such, the potential of sweetener-stimulation of T1R2-T1R3 leading to upregulation of SGLT1 allows the provision of more glucose (energy) and hydration for horses. This is especially important when the need for glucose increases during strenuous exercise, pregnancy, and lactation. There are significant differences amongst species in the ability to detect sweeteners. Amino acid substitutions and pseudogenization of taste receptor genes underlie these variations. Nothing is known about the sweetener specificity of horse T1R2-T1R3. Using heterologous expression methodology, we demonstrate that sweeteners sucralose, stevia and neohesperidin dihydrochalcone (NHDC) activate horse T1R2-T1R3, but cyclamate does not. Determination of sweetener specificity of equine sweet receptor is crucial for developing suitable dietary additives to optimize glucose absorption, hydration and avoiding the intestinal disease brought about by microbial fermentation of unabsorbed carbohydrate reaching the large intestine.